2014
DOI: 10.11118/actaun201462050897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prepartum Supplementation of Yeast Culture (Saccharomyces Cerevisiae) on Biochemical Parameters of Dairy Cows and Their Newborn Calves

Abstract: The aim of our experiment was to compare the effect of different levels of the addition ofSaccharomyces cerevisiae (S. c.)yeast culture on feed carrier to the current ration MK DOJ Levucell SC 20, Saccharomyces cerevisiae CNCM I-1077 (E 1711) 20.1010CFU on the blood parameters of high-pregnant breeding cows and their calves. The experiment included 42 breeding cows of the Czech Fleckvieh cattle breed and their calves. The breeding cows were divided into two age groups, each of 21 heads. The first group include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
6
6
0
Order By: Relevance
“…The present results concerning reducing the activity of serum AST and ALT of cows and their calves in G3 is in agreement with Hammon and Blum (1998), who reported a relationship between AST and ALT activity in calf blood and the suckled milk quality. Generally, the positive effects of YC treatment on improvement of blood biochemicals are in agreement with Ghoneem and Mahmoud (2014) and Fröhdeová et al (2014).…”
Section: Blood Biochemical Concentrationssupporting
confidence: 65%
See 1 more Smart Citation
“…The present results concerning reducing the activity of serum AST and ALT of cows and their calves in G3 is in agreement with Hammon and Blum (1998), who reported a relationship between AST and ALT activity in calf blood and the suckled milk quality. Generally, the positive effects of YC treatment on improvement of blood biochemicals are in agreement with Ghoneem and Mahmoud (2014) and Fröhdeová et al (2014).…”
Section: Blood Biochemical Concentrationssupporting
confidence: 65%
“…Yeast has positive effects on animal blood hematology, which was reflected in general health status improvement (Agazzi et al, 2014). Also, several investigations found that, immunity of dairy cows was improved in terms of increasing the blood protein and its fractions, and decreasing AST and ALT activity in blood cows treated with yeast (Fröhdeová et al, 2014, Tóthová et al, 2014Wafa, 2017). The present study aimed to evaluate the productive and reproductive performance, and blood constitutes of heifers at first reproductive season as affected by feeding on ration containing different levels of yeast culture…”
Section: Introductionmentioning
confidence: 99%
“…According to the present results, the highly significant increase in calves blood plasma IgA, IgG and IgM immediately after birth up to the 3rd dayresulted from increasing immunoglobulin levels in the colostrum of dams fed YC and LB combination diet (G4). These results are in agreement with Fröhdeová et al (2014), which found that the lower amount of Saccharomyces cerevisiae addition to higher lactating cows led to increasing the level of cows serum IgG and then the level of IgG in serum their calves. Also, similar effects were reported by some previous investigations after the ration supplementation with prebiotics in different species (Franklin et al, 2002;Spearman, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…The obtained results in this study indicated heavier calves at birth in all groups of dams treated with LB or YC than in control group that fed non-supplemented diet which may be attributed to the improvement in immune, health status and weight of their dams (Wafa, 2017). Fröhdeová et al, (2014) indicated that, the addition of low amount of Saccharomyces cerevisiae increased the level of IgG in serum at higher lactating cows. Also, similar effects were reported by some previous investigations after feed supplementation with prebiotics in different species (Franklin et al, 2002;Spearman, 2004).…”
Section: Immunogloblins Concentrations In Colostrumsupporting
confidence: 49%